2009
DOI: 10.1177/0961203309348234
|View full text |Cite
|
Sign up to set email alerts
|

The numbers of Foxp3 + Treg cells are positively correlated with higher grade of infiltration at the salivary glands in primary Sjögren's syndrome

Abstract: This study was designed to investigate whether Foxp3( +) regulatory T (Treg) cells play a role in the histopathologic changes of primary Sjögren's Syndrome (pSS) and to evaluate other factors possibly associated with Foxp3(+) Treg cells in pSS patients. The number of FoxP3-expressing T cells in peripheral blood (PB) of 39 patients with pSS, 40 patients with rheumatoid arthritis (RA), and 28 healthy controls was measured by flow-cytometer analysis. FoxP3-expressing CD4(+)CD25(+) Treg cells were analyzed in mino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 33 publications
(40 reference statements)
3
51
1
1
Order By: Relevance
“…Subsequent studies focused on evaluating the possible involvement of T REG in the human manifestations of these pathologies in order to identify phenotypic and/or functional alterations of these cells during the disease course. Data published on Sjögren's syndrome (SS), are all substantially in agreement that the percentages of peripheral blood of T REG cells, identified by high CD25 expression and/or expression of FoxP3, of affected patients are identical to or slightly lower than those of healthy controls (15)(16)(17)(18). Furthermore, extremely interesting results are emerging from immunohistochemical studies of the salivary glands in SS.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Subsequent studies focused on evaluating the possible involvement of T REG in the human manifestations of these pathologies in order to identify phenotypic and/or functional alterations of these cells during the disease course. Data published on Sjögren's syndrome (SS), are all substantially in agreement that the percentages of peripheral blood of T REG cells, identified by high CD25 expression and/or expression of FoxP3, of affected patients are identical to or slightly lower than those of healthy controls (15)(16)(17)(18). Furthermore, extremely interesting results are emerging from immunohistochemical studies of the salivary glands in SS.…”
mentioning
confidence: 56%
“…Furthermore, extremely interesting results are emerging from immunohistochemical studies of the salivary glands in SS. These show a correlation between the lymphocytic infiltrate of the salivary glan-original article Expansion of CD4+CD25-GITR+ regulatory T-cell subset in the peripheral blood of patients ds (evaluated both by the Chisholm score and by the focus score) and the number of T REG cells present in the saliva (16)(17)(18). In other words, even though the presence of a T REG cell population has been observed at the site of inflammation, these cells do not seem to be able to reduce the lymphocytic infiltrate or, consequently, the parenchymal damage caused by it.…”
mentioning
confidence: 99%
“…The mechanisms regulating the increase in FOXP3 + Treg numbers in M2 and M3 stages of celiac disease, which are similar to those described by others for salivary gland tissue of primary Sjögren's syndrome [27] , are not fully understood. It is one possibility that there is a general increase in lymphocyte activation and expansion which is regulated by proinflammatory cytokines during advanced stages of celiac disease [28] .…”
Section: Discussionmentioning
confidence: 91%
“…Concerning Foxp3-i-Tregs in SS, several reports suggested that the numbers of Foxp3+ Tregs are positively correlated with SS (11,12). Sarigui et al (11) reported that Foxp3+ Tregs were enriched in the salivary glands and associated with the Chisholm score in primary SS.…”
Section: Discussionmentioning
confidence: 98%